2009
DOI: 10.1371/journal.pone.0007381
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of Antibody Isotype and Subclass Responses to Plasmodium falciparum Antigens

Abstract: BackgroundIt is important to understand the extent to which genetic factors regulate acquired immunity to common infections. A classical twin study design is useful to estimate the heritable component of variation in measurable immune parameters.Methodology/Principal FindingsThis study assessed the relative heritability of different plasma antibody isotypes and subclasses (IgG1, IgG2, IgG3, IgG4, IgM, IgA and IgE) naturally acquired to P. falciparum blood stage antigens AMA1, MSP1-19, MSP2 (two allelic types) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…Interestingly, the Tanzanian study and several others (Dobano et al, 2012; Stanisic et al, 2009a) document a predominance of IgG1 over IgG3 for MSP-1 and AMA-1 in areas of moderate and high transmission, whereas we observed a clear IgG3 bias to these as well as to pre-erythrocytic antigens in the area of high, stable transmission. A number of other studies (Courtin et al, 2009; Dodoo et al, 2008; Duah et al, 2010; Duah et al, 2009; Kinyanjui et al, 2003; Richards et al, 2010), including our previous evaluations of CSP, TRAP and LSA-1 in another unstable transmission area of Kenya (John et al, 2003), have also shown an IgG3 bias over IgG1 to P. falciparum antigens. Such bias is somewhat unexpected, as IgG3 antibodies have a shorter half-life than other subclasses.…”
Section: Discussionmentioning
confidence: 59%
“…Interestingly, the Tanzanian study and several others (Dobano et al, 2012; Stanisic et al, 2009a) document a predominance of IgG1 over IgG3 for MSP-1 and AMA-1 in areas of moderate and high transmission, whereas we observed a clear IgG3 bias to these as well as to pre-erythrocytic antigens in the area of high, stable transmission. A number of other studies (Courtin et al, 2009; Dodoo et al, 2008; Duah et al, 2010; Duah et al, 2009; Kinyanjui et al, 2003; Richards et al, 2010), including our previous evaluations of CSP, TRAP and LSA-1 in another unstable transmission area of Kenya (John et al, 2003), have also shown an IgG3 bias over IgG1 to P. falciparum antigens. Such bias is somewhat unexpected, as IgG3 antibodies have a shorter half-life than other subclasses.…”
Section: Discussionmentioning
confidence: 59%
“…Allelic differences in these genes exhibited contradictory results among the various investigated endemic areas, including Brazil; therefore, it seems unlikely that they are the only mechanism responsible for deviations of the immune response [49][50][51].…”
Section: Genetic Variability Of Il-2 and The Physiopathogenesis Of Pamentioning
confidence: 98%
“…There is evidence that host genetic factors influence antibody responses to both vaccines (eg varicella and rubella) 1,2 and to naturally occurring infections such as malaria, Chagas, and Epstein-Barr virus. [3][4][5] We previously demonstrated that differences in antibody titer, which reflect infection history, are significantly heritable for a number of common infectious pathogens. 6 Here we attempt to localize the genetic factors influencing serological phenotypes of these pathogens using genome-wide statistical gene-mapping approaches.…”
Section: Introductionmentioning
confidence: 99%